My mother wore a yellow dress : an Irish childhood in the 1960s - McKenna, Christina, 1957- (Glasgow : Neil Wilson, 2004)
'I learned about conflict from my parents.' So begins Christina McKenna's haunting memoir of her lonely early life. Recounting scenes from her chlldhood in Ulster, she paints a memorable and poignant picture of violence and oppression with her brutal father and protective mother, whose retaliation to her husband's meanness came in the form of a secret yellow dress. At age eleven, she experiences a frightening supernatural occurrence, a prolonged haunting that confirms for her the reality of the spirit world. Though it affects her deeply, she later learns to channel her confusion into twin
Keywords: McKenna, Christina, -- 1957- -- Childhood and youth; Mothers and daughters -- Northern Ireland -- Biography; Northern Ireland -- Biography